Social Classification - Need For Constant Updating - Kumar P (Wolters Kluwer Medknow Publications, 1993)
Socio-economic status influences the health of individuals and also the utilization of available health facilities. Of several available parameters, such as income, occupation, education, religion, caste, place of residence etc., the per capita monthly income has been the basis of the Prasadâ€s social classifications which is most commonly used in Indian studies. With inflationary trends of the economy this classification needs constant revision. An attempt has been made to link it with the all India consumer price index (AICPI) and a modified classification has been proposed with a built â€" in provision of its upgrading from time to keep it relevant and useful.